A double diamond model-based approach to the innovative design of mobility scooters for the older adults - Wang, Xianzhi; Zhao, Zefeng; Yuan, Hang; Ai, Huijuan (Frontiers in Public Health, 2025)
IntroductionThe global trend of population aging is irreversible, and the safety of older adults mobility has become an increasing concern. In response to the gap between rapidly growing market demand and limited academic research, this study proposes a design methodology for older adults mobility scooters guided by the four stages of the Double Diamond model.MethodsIn the Discover stage, core user requirements were identified through user behavior observation and the Kano model. In the Define stage, multi-criteria decision-making (MCDM) was used to calculate the weight of each requirement. In the Develop stage, Quality Function Deployment (QFD) translated high-priority user needs into technical features and calculated their hierarchical weights. In the Deliver stage, these technical features were further translated into concrete design solutions.ResultsThis study provides a comprehensive and systematic framework for the innovative design of older adults mobility scooters. It aims to enhance the feasibility and design efficiency of older adults mobility products and contribute to addressing the challenges of population aging.